Multiscale microsphere modelling of open-cell metal foams enriched by statistical analysis of geometric parameters. (March 2020) - Bleistein, T.; Reis, M.; Cheng, X.; Redenbach, C.; Diebels, S.; Jung, A.
Highlights: Scale bridging approach for open cell metal foams using a microsphere model. Innovative model linking the macroscopic behaviour and the microstructure. Enriched microsphere theory by statistically analysed geometry parameters. Macroscopic simulation exclusively using microscopically characterised quantities. Graphical abstract: Abstract: Tailored design of application-optimised foam components requires the prediction of the mechanical properties by a numerical simulation model. Simulations that are able to account for microstructural changes are very time-consuming and not efficient. Hence, scale-bridging must be applied between the application-specific macroscale and the microscale or mesoscale accounting for structural variations in the pore or strut geometry. The present contribution deals with an innovative microsphere model considering uniaxial microtensile and microcompression experiments on individual struts as 1D constitutive laws for the microsphere model. This model is complemented by a statistical analysis of a real foam geometry and generalises the constitutive 1D models to a macroscopic 3D model taking the microstructure into account. The model was successfully validated by macroscopic experiments. The validation shows the potential of the model to predict the macroscopic behaviour of the foam using only data at the microscopic level. Thus expensive experiments on complete components can be reduced.